BAC cloning and heterologous expression of a giant biosynthetic gene cluster encoding antifungal neotetrafibricin in streptomyces rubrisoli - Park, Heung-Soon; Park, Ji-Hee; Kim, Hye-Jin; Kang, Seung-Hoon; Choi, Si-Sun; Kim, Eung-Soo (Frontiers in Bioengineering and Biotechnology, 2022)
Polyene natural products including nystatin A1, amphotericin B, ECO-02301, and mediomycin belong to a large family of valuable antifungal polyketide compounds typically produced by soil actinomycetes. A previous study (Park et al., 2021) isolated Streptomyces rubrisoli Inha501 with strong antifungal activity and analyzed a large-sized biosynthetic gene cluster (BGC) of a linear polyene compound named Inha501-neotrafibricin (I-NTF) using whole genome sequencing and bioinformatics. In the present study, an entire I-NTF BGC (~ 167 kb) was isolated through construction and screening of Streptomyces BAC library. Overexpression of the cloned I-NTF BGC in the wild-type S. rubrisoli Inha501 and its heterologous expression in S. lividans led to 2.6-fold and 2.8-fold increase in I-NTF yields, respectively. The qRT-PCR confirmed that the transcription levels of I-NTF BGC were significantly increased in both homologous and heterologous hosts containing the BAC integration of I-NTF BGC. In addition, the I-NTF aglycone-producing strains were constructed by a target-specific deletion of glycosyltransferase gene present in I-NTF BGC. A comparison of the in vitro biological activities of I-NTF and aglycone I-NTF confirmed that the rhamnose sugar motif of I-NTF plays a critical role in both antifungal and antibacterial activities. These results suggest that the Streptomyces BAC cloning of a large-sized natural product BGC is a valuable approach for natural product titer improvement and biological activity screening of natural product in actinomycetes.